DAMPAK ARTIFICIAL INTELLIGENCE (AI) TERHADAP JABATAN FUNGSIONAL PENERJEMAH DAN IMPLIKASINYA PADA PERENCANAAN SUMBER DAYA MANUSIA DI SEKTOR PUBLIK - Anastasia Faradila Hakim; Nia Pertiwi; Muh. Asdig Fanani (Epigram, 2025)
The advancement of artificial intelligence technology has sparked a discourse on the future relevance of the translation profession, including the functional position of translators within the public sector. This disruptive phenomenon poses significant challenges to existing human resource planning practices. This research aims to analyze the impact of artificial intelligence on the Functional Position of Translators and to formulate adaptive human resource planning strategies to ensure the position's relevance. The research method employed is descriptive qualitative with a multi-method approach, combining a systematic literature review and in-depth interviews with practitioners and representatives from the fostering institution. Data analysis was conducted using the theoretical frameworks of Strategic Human Resource Management, Disruptive Innovation Theory, and the Resource-Based View. The results indicate that artificial intelligence acts as a disruptive innovation, transforming the translator's role from a producer of translations to a validator of quality and a context specialist. Human competencies such as understanding cultural nuances, ethics, and critical thinking are strategic resources that are difficult for technology to imitate. In conclusion, the future of the Functional Position of Translators lies not in rejecting technology, but in the synergistic collaboration between humans and machines. This implies an urgent need to reform the pillars of human resource planning, from job analysis and recruitment to career development, to align with the demands of the digital era.